Exploring masculinity - Bhasin, Kamla (Gender basics, 2004)
Why is everyone talking about masculinity these days? What exactly do we mean by it? Is there only one kind of masculinity or do we have to deal with many masculinities? This lucidly written pamphlet explores the meaning of masculinity and its importance for gender relations, social arrangements, political and economic systems, and religious and family ideologies. It looks at: hegemonic masculinity, militant masculinity, working class and bourgeois masculinity; it examines the link between masculinism and militarism; between communalism, fundamentalism and masculinism; and capitalism and masculinism. It highlights the impact of negative masculinity and femininity on women and men, both, and suggests alternatives for transforming gender relations. All presented in the author's inimitable question-and-answer style.